2020
DOI: 10.1088/2053-1591/ab7266
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and tribological characterization of niobium boride coating produced on AISI 1020 steel via multicomponent boriding

Abstract: Niobium boride coating was produced on AISI 1020 steel by multicomponent boriding process. Boriding treatment at1000°C for 4 h was followed by thermo-reactive diffusion technique at 1000°C for 6 h under argon atmosphere. Microabrasive wear tests were carried out using SiC abrasive particles at slurry concentrations of 0.5 and 1.0 g cm −3 . Normal loads of 0.49 and 0.98 N were used. NbB and Nb 5 B 6 phases were identified by XRD analysis. The niobium boride coating thickness was 2.0±0.5 μm and its hardness wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…The examination of the borided coating layer morphologies showed the existence of a compact layer structure and a clearly visible interface between the matrix and the borided layer is clearly visible and the layer has a compact structure. While a saw-toothed morphology was reported for the boride layer in the previous studies due to the low concentration of carbon [12,22,23], a planar morphology was observed in this study due to high alloy ratios of the materials, as shown in the literature [24,25]. As the carbon content of the matrix material and the ratio of the alloying elements increase, a more planar morphology was encountered, as the toothed structure expected to form on the matrix interface of the boride layer was suppressed [26].…”
Section: Resultsmentioning
confidence: 99%
“…The examination of the borided coating layer morphologies showed the existence of a compact layer structure and a clearly visible interface between the matrix and the borided layer is clearly visible and the layer has a compact structure. While a saw-toothed morphology was reported for the boride layer in the previous studies due to the low concentration of carbon [12,22,23], a planar morphology was observed in this study due to high alloy ratios of the materials, as shown in the literature [24,25]. As the carbon content of the matrix material and the ratio of the alloying elements increase, a more planar morphology was encountered, as the toothed structure expected to form on the matrix interface of the boride layer was suppressed [26].…”
Section: Resultsmentioning
confidence: 99%
“…In order to prove that the wear crater produced during the micro-scale abrasive wear tests reflected the counter-body geometry, i. e., a ball of 12.7 mm radius, the topographical analysis of the wear craters was carried out for each condition of the wear tests. In Figure 7 it is shown the Zn + nano-coating condition abraded with an abrasive slurry concentration of 0.244 g/cm³ at an applied load of 0.98 N. As can be seen from Figure 7(b), the wear crater has a radius of 12.696 mm, thus validating the use of Formula (1) [27,28].…”
Section: Tribological Behaviormentioning
confidence: 61%
“…The Tribology research group of Universidade do Estado de Santa Catarina (UDESC) has conducted research on Tribology, Surface Engineering and Powder Metallurgy since 2009. The group develops studies considering improving materials' tribological behaviour through surface changes, increasing materials' tribological performance, especially in parts produced by powder metallurgy [333,[358][359][360][361][362][363][364]. The group has been developing niobium-based tool materials (cermets) [365][366][367][368] and zinc-aluminium alloys [369].…”
Section: Brazilian Tribology: Status Quomentioning
confidence: 99%